Association of Digoxin Application Approaches With Long-Term Clinical Outcomes in Rheumatic Heart Disease Patients With Heart Failure: A Retrospective Study - Liu, Cheng; Lai, Yanxian; Guan, Tianwang; Zeng, Qingchun; Pei, Jingxian; Zhang, Shenghui; Wu, Daihong; Wu, Deping (Frontiers in Cardiovascular Medicine, 2021)
Objective: This retrospective, case–control study was executed to assess the effects of digoxin (DGX) use approaches [continuous use of DGX (cDGX) vs. intermittent use of DGX (iDGX)] on the long-term prognosis in rheumatic heart disease (RHD) patients with heart failure (HF). Methods: A total of 642 RHD patients were enrolled to this study after propensity matching. The associations of DGX application approaches with the risks of all-cause mortality, cardiovascular death (CVD), HF re-hospitalization (1-, 3-, and 5-year), and new-onset atrial fibrillation (AF) were analyzed by multivariate Cox proportional hazards or binary logistic regression models, respectively. Results: cDGX was associated with increased risks of all-cause mortality (adjusted HR = 1.84, 95% CI: 1.27–2.65, P = 0.001) and CVD (adjusted HR = 2.23, 95% CI: 1.29–3.83, P = 0.004) in RHD patients with HF compared to iDGX. With exception of 1-year HF re-hospitalization risk, cDGX was associated with increased HF re-hospitalization risk of 3-year (adjusted OR = 1.53, 95% CI: 1.03–2.29, P = 0.037) and 5-year (adjusted OR = 1.61, 95% CI: 1.05–2.50, P = 0.031) as well as new-onset AF (adjusted OR = 2.06, 95% CI: 1.09–3.90, P = 0.027). Conclusion: cDGX was significantly associated with increased risks of all-cause mortality, CVD, medium-/long-term HF re-hospitalization, and new-onset AF in RHD patients with HF.